Implementasi Penggunaan Artificial Intelligence pada Pembelajaran PAI di SD Muhammadiyah Pendowoharjo - Muh. Abdul Hafidz S; Muhammad Hafizh Rifaldi; Alfikri Rifzatul Akbar; Ferdiandi Ambotuo Sangkang; Lovandri Dwanda Putra (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to describe the implementation of Artificial Intelligence (AI) in Islamic Religious Education (PAI) learning at Muhammadiyah Pendowoharjo Elementary School. The background of the study is based on the need for PAI learning innovation that is able to adapt to the development of digital technology, but remains based on Islamic values ​​and the formation of students' religious character. The study uses a descriptive qualitative approach with primary data sources through interviews, observations, and documentation. The research subjects consisted of PAI teachers and class teachers who implemented AI-based learning. The results of the study indicate that the use of AI functions as a learning aid that supports teachers in developing teaching materials, presenting PAI materials visually and interactively, and increasing work efficiency. AI-based applications such as ChatGPT and Gemini are used in a limited and controlled manner, while still using textbooks and official sources as the main references. Teachers have a central role in controlling, verifying, and filtering information generated by AI to suit Islamic values ​​and the characteristics of elementary school students. The implementation of AI has a positive impact on student interest, motivation, and engagement, while fostering digital literacy from an early age. However, AI does not replace the role of teachers in shaping morals, etiquette, and religious character. Therefore, AI integration can be an effective learning innovation when used wisely, purposefully, and proportionally.